Analysis of differential interests: A quantitative approach to learning method preferences between religious-nonreligious and institutes-universities - Dzikril Ikhsan; Ahmad Jamin; Albertos Damni (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
This study endeavors to scrutinize student contentment levels regarding pedagogical approaches utilized by educators amidst the backdrop of the Fourth Industrial Revolution, with a particular emphasis on students categorized by their fields of study and institutional affiliations. Data were collated from 123 student participants drawn from diverse universities within the Province of Jambi. This research used a structured online questionnaire to acquire data in employing a quantitative methodology. Data analysis involved the utilization of a Likert scale to gauge the degree of student satisfaction. Assumption testing was used to analyze the Likert scale. In this study, assumption testing using independent sample t-tests, also viewed through the acquisition of proportion values, was used to determine how differences in satisfaction levels were found. Findings reveal noteworthy student satisfaction concerning instructional methodologies, notably in punctuality, subject matter proficiency, instructional delivery, and assessment and evaluation procedures. Moreover, evaluating instructor performance, as perceived by students vis-à-vis their respective majors and institutional statuses, substantially impacts satisfaction levels with pedagogical strategies across various facets of the learning process. The cumulative average significance of overall satisfaction with instructional methodologies among students enrolled in universities within Jambi. Nonetheless, areas necessitating enhancement, such as evaluation and assessment practices, alongside fostering emotional rapport between students and instructors, are underscored as imperative for promoting an optimal learning environment.